Multiculturalism, crime, and criminal justice - McNamara, Robert Hartmann (Oxford University Press, 2018)
Introduction -- Group dynamics, communication, and social interaction -- African Americans and the criminal justice system -- Hispanic Americans and the criminal justice system -- Asian Americans and the criminal justice system -- Native American and the criminal justice system -- Women and the criminal justice system -- The gay community and the criminal justice system -- The elderly and the criminal justice system -- Youth culture and the criminal justice system -- Policing and multiculturalism -- Courts and multiculturalism -- Corrections and multiculturalism -- Preparing for multiculturalism and diversity : training and policy -- The future of multiculturalism : strategies for success